Soil-Geomorphological Mapping Using Landsat-9 Imagery and GIS in West Muna Regency, Indonesia - Tahir Tahir; Daud Yusuf (Jambura Geoscience Review, 2026)
Accurate soil-type information is essential for land-resource planning, yet spatial soil data for West Muna Regency remain limited for supporting land-use zoning. Recent advances in remote sensing and geographic information systems (GIS) have strengthened soil mapping by enabling more efficient acquisition, processing, analysis, and presentation of spatial data. This study applies integrated remote sensing and GIS, supported by a soil-geomorphological approach, to identify and map the spatial distribution of soil characteristics in West Muna Regency. The objectives of this study are to identify soil-type distribution, analyze soil texture and surface-drainage patterns, and interpret these characteristics in relation to geomorphological units and land-use planning needs. Landsat-9 imagery was interpreted together with landform analysis, GIS-based spatial overlay, field observation, and laboratory analysis of soil characteristics. The results show that soils in West Muna Regency are classified into three soil orders: Inceptisols, Alfisols, and Entisols. Swampy alluvial plains and coastal alluvial plains are dominated by relatively fertile sandy clay soils, whereas rocky coastal areas are characterized mainly by marine sand deposits with lower nutrient status. Spatial analysis indicates that Inceptisols occupy the largest area, covering 71,250.04 ha or 78.65% of the regency, followed by Alfisols with 11,923.42 ha or 13.16%, and Entisols with 7,414.15 ha or 8.18% of total area. These findings indicate that soil distribution is closely related to landform, parent material, soil texture, and drainage condition. The integrated soil-geomorphological approach provides practical spatial information for regional soil-resource assessment and land-use planning in West Muna Regency.